PENGARUH SISTEM BAGI HASIL TERHADAP KEPUASAN NASABAH PADA BMT NU JATIM CABANG MLANDINGAN - Ahmad Sahidah; Mugyena Mugyena (Pusat Riset dan Inovasi Nasional, 2025)
The Profit Sharing System is one of the main mechanisms in Islamic banking and financial institutions, where profits and risks are shared between the institution and customers based on a predetermined agreement. This study aims to determine the effect of the Profit Sharing System on customer satisfaction at BMT NU Jatim Mlandingan Branch. The method used in this study is a quantitative method with an accidental sampling technique because this method is more practical, easy to apply and efficient in terms of time and cost. Data were obtained through questionnaires distributed to respondents who were customers of BMT NU Jatim Mlandingan Branch. Data analysis was carried out using correlation and significance tests with the help of SPSS software. The results showed that the Profit Sharing System had a correlation with customer satisfaction of 0.280. However, based on the statistical significance test, the P-value of 0.112 (> 0.05) indicated that the effect was not significant. This indicates that the Profit Sharing System is not the only factor that determines customer satisfaction. The conclusion of this study is that although the Profit Sharing System has an effect on customer satisfaction, other factors such as service quality, trust in the institution, and the facilities provided are likely to play a greater role in determining the level of customer satisfaction. Therefore, further research is needed to identify other factors that are more dominant in increasing customer satisfaction at BMT NU Jatim, Mlandingan Branch.